Pengembangan Lembar Kerja Siswa Matematika Berbasis Contextual Teaching and Learning Berbantuan QR Code pada Siswa Kelas V Sekolah Dasar - Rosalina, Elya; Sukenda Egok, Asep (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to 1) develop the design of contextual teaching and learning-based mathematics student worksheets with the assistance of QR codes for fifth graders in elementary schools, and 2) test the validity and practicability of mathematics student worksheets based on contextual teaching and learning with the assistance of QR codes for Grade V students in schools. The method in this study refers to the development of Contextual Teaching and Learning Based Mathematics Student Worksheets Assisted by QR Code with the design and development of learning modules using a 4-D development model with four stages: definition (define), planning (design), development (development), and deployment (disseminate). According to the research findings, the Mathematics Student Worksheet Based on Contextual Teaching and Learning Assisted with the QR Code, which has been corrected based on the calculation of the questionnaire filling data with an average score of 0.85 and has been adjusted to the validity interpretation of Aiken's V, is included in the category > 0.80 with information high or can be said to be valid. In addition, the results of the researcher's practicality analysis demonstrate that the data obtained an average score of 94.64% when adjusted for the practicality criteria of the Student Worksheets, putting it in the extremely practical group. The result is that Mathematics Student Worksheets Based on Contextual Teaching and Learning Aided by QR Code are suitable for use in the learning process. Keywords: Contextual Teaching and Learning, Mathematics LKS